Characteristics of the ammonium ion adsorption from wastewater by the activated carbon obtained from waste tire - Ghising, Ram; Jha, Vinaya (Journal of Nepal Chemical Society, 2022)
The activated carbons were prepared from waste tire using a pyrolysis technique in different environments, namely: activated carbon in the open air (AC-O), nitrogen gas (AC-N), nitrogen gas and water steam (AC-NW), and a composite of tire and aluminum hydroxide in nitrogen and steam atmosphere (AC-COM), in order to study the change in specific surface area and making the composite of activated carbon and alumina. The X-ray diffraction study revealed the presence of quartz, alumina, zinc sulfide, and activated carbon. Methylene blue adsorption isotherm showed that the highest specific surface area of 218m2/g was found in the case of activated carbon prepared in an oxygen atmosphere and subsequently used for ammonium ion adsorption. The adsorption isotherm and kinetic behavior were studied with optimum pH 9. The adsorption isotherm fitted well to the Freundlich Model than that of Langmuir and the equilibrium monolayer adsorption capacity calculated from Langmuir was 277.8mg/g at room temperature. The adsorption reached equilibrium in 120 minutes, and kinetic data fitted well to the pseudo-second-order model with a rate constant value 5.3×10-3 L g/(mg·min). Real water samples from different places within Kathmandu valley were subjected to ammonium ion adsorption onto the active carbon and were worked for the adsorption smoothly